Graphene oxide induces canonical Wnt/β-catenin signaling-dependent toxicity in Caenorhabditis elegans. (March 2017) - Zhi, Lingtong; Qu, Man; Ren, Mingxia; Zhao, Li; Li, Yunhui; Wang, Dayong
Abstract: The potential adverse effects of graphene oxide (GO) on organisms have received great attention. However, the underlying molecular mechanisms for response to GO exposure are still largely unclear. Canonical Wnt/β-catenin signaling is an evolutionarily conserved signaling, and plays a key role in the development. Using assay system of Caenorhabditis elegans, we investigated the potential involvement of canonical Wnt/β-catenin signaling pathway in the regulation of response to GO. GO exposure caused the damage on the functions of both primary and secondary targeted organs by dysregulating the expression of β-catenin BAR-1, APR-1 and GSK-3 in APC complex, Dishevelled proteins of DSH-1, and DSH-2, and Frizzled receptors of MOM-5 and CFZ-2 in the Wnt/β-catenin signaling pathway. Based on genetic evidence, we further raised a signaling cascade of MOM-5/CFZ-2-DSH-1/DSH-2-APR-1/GSK-3-BAR-1 in the Wnt/β-catenin signaling pathway in the regulation of GO toxicity. The homeobox protein EGL-5, an important downstream target of Wnt/β-catenin signaling, regulated GO toxicity by modulating expression of the genes required for the control of oxidative stress. Moreover, β-catenin BAR-1 acted in parallel with insulin or p38 MAPK signaling to regulate the GO toxicity. Therefore, our results suggest the crucial function of Wnt/β-catenin signaling pathway in the regulation of GO toxicity in organisms. Graphical abstract: In this study, we found that graphene oxide (GO) could potentially dysregulate Wnt/β-catenin mediated developmental signaling. Moreover, a signaling cascade of MOM-5/CFZ-2-DSH-1/DSH-2-APR-1/GSK-3-BAR-1 in canonical Wnt/β-catenin signaling pathway was raised to be required for the control of GO toxicity, which may function in parallel with the insulin or p38 MAPK signaling pathway.